The Xer activation factor of TLCΦ expands the possibilities for Xer recombination. Issue 11 (3rd June 2022) - Miele, Solange; Provan, James Iain; Vergne, Justine; Possoz, Christophe; Ochsenbein, Françoise; Barre, François-Xavier
Abstract: The chromosome dimer resolution machinery of bacteria is generally composed of two tyrosine recombinases, XerC and XerD. They resolve chromosome dimers by adding a crossover between sister copies of a specific site, dif . The reaction depends on a cell division protein, FtsK, which activates XerD by protein-protein interactions. The toxin-linked cryptic satellite phage (TLCΦ) of Vibrio cholerae, which participates in the emergence of cholera epidemic strains, carries a dif -like attachment site ( attP ). TLCΦ exploits the Xer machinery to integrate into the dif site of its host chromosomes. The TLCΦ integration reaction escapes the control of FtsK because TLCΦ encodes for its own XerD-activation factor, XafT. Additionally, TLCΦ attP is a poor substrate for XerD binding, in apparent contradiction with the high integration efficiency of the phage. Here, we present a sequencing-based methodology to analyse the integration and excision efficiency of thousands of synthetic mini-TLCΦ plasmids with differing attP sites in vivo . This methodology is applicable to the fine-grained analyses of DNA transactions on a wider scale. In addition, we compared the efficiency with which XafT and the XerD-activation domain of FtsK drive recombination reactions in vitro . Our results suggest that XafT not only activates XerD-catalysis but also helps form and/or stabilize synaptic complexes between imperfect Xer recombination sites.